2017
DOI: 10.1088/1361-651x/aa6f4f
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of point defect production inα-quartz using molecular dynamics simulations

Abstract: Molecular dynamics (MD) simulations are performed to investigate the production of point defects in α-quartz by oxygen and silicon primary knock-on atoms (PKAs) of 0.25–2 keV. The Wigner–Seitz (WS) defect analysis is used to identify the produced vacancies, interstitials, and antisites, and the coordination defect analysis is used to identify the under and over-coordinated oxygen and silicon atoms. The defects at the end of the ballistic phase and the residual defects, after annealing, increase with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
4
4
0
Order By: Relevance
“…The accuracy of this potential has been confirmed in prior work [52,56]. Results showed that the lattice and elastic constants, density, equations of state, as a function of temperature and pressure, and energies of defect formation are in good agreement with reported experimental results by others [52,56]. A limitation of the ionic potentials, such as one used in this present work, is overestimating the melting point.…”
Section: Methodssupporting
confidence: 86%
See 3 more Smart Citations
“…The accuracy of this potential has been confirmed in prior work [52,56]. Results showed that the lattice and elastic constants, density, equations of state, as a function of temperature and pressure, and energies of defect formation are in good agreement with reported experimental results by others [52,56]. A limitation of the ionic potentials, such as one used in this present work, is overestimating the melting point.…”
Section: Methodssupporting
confidence: 86%
“…This potential gives displacement probability distributions that are nearly identical to those reported using a splined Buckingham-ZBL potential [52]. The accuracy of this potential has been confirmed in prior work [52,56]. Results showed that the lattice and elastic constants, density, equations of state, as a function of temperature and pressure, and energies of defect formation are in good agreement with reported experimental results by others [52,56].…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…Among them only some hole-like paramagnetic defects associated with silicon vacancies have been fully investigated [19,20]. Full knowledge of the nature of defects and dynamic properties (e.g., radiation dose dependence and thermal stability) is necessary for theoretic simulations of the damage process in neutron-irradiated quartz structure [21][22][23]. Also radiation-induced defects in natural quartz are useful for dating [24] and mineral exploration [25,26].…”
mentioning
confidence: 99%